CFD Analysis of Empty Fruit Bunch Drying System in Biomass Processing Application - Wan Muzzaffar Amin,; Amirnordin, Shahrin Hisham; Mohd Faizal Mohideen Batcha,; Ahmad Jais Alimin,; Shahrul Azmir Osman,; Azian Hariri,; Amir Khalid,; Mohd Faizal Tukimon,; Makatar Wae-hayee,; Mohammad Faizal Jabbar, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The global shift towards biomass energy reflects the growing recognition of its potential to provide clean and renewable energy while reducing carbon emissions and promoting environmental sustainability. Empty Fruit Bunch (EFB), a by-product of the palm oil industry, has emerged as a promising biomass fuel source; however, its high moisture content significantly reduces combustion efficiency, necessitating an effective drying process. This study examines the heat transfer and thermal characteristics within a drum dryer system used for EFB drying, aiming to determine the optimal inlet air temperature and velocity for efficient moisture removal. A three-dimensional model of the EFB drum dryer was designed using SolidWorks, and computational fluid dynamics (CFD) simulations were performed using ANSYS software. The inlet air temperature ranged from 120°C to 250°C, with a volume flow rate between 0.105 m³/s and 0.185 m³/s. Results indicate that increasing both inlet temperature and air velocity enhances the outlet air temperature, whereas the inlet flow rate mainly influences the outlet velocity. The highest outlet temperature achieved was 64.17°C, suggesting that the tested operating conditions were insufficient to achieve optimal drying efficiency. These findings provide valuable insights for scaling up the system under modified operating parameters or reducing the dryer length to minimize heat loss and improve drying performance.